2016
DOI: 10.18549/pharmpract.2016.04.830
|View full text |Cite
|
Sign up to set email alerts
|

Simplification of HAART therapy on ambulatory HIV patients in Malaysia: a randomized controlled trial

Abstract: Objective:Evaluate the impact of fixed-dose combination (FDC) containing emtricitabine (FTC), tenofovir (TDF), and efavirenz (EFV) versus a free-dose combination (FRC) of the same three drugs on clinical outcomes, adherence and quality of life in Malaysian outpatients with HIV.Methods:HIV patients (n=120) on highly active antiretroviral therapy (HAART) in the infectious disease clinic of Hospital Sungai Buloh were randomized to either FDC (n=60) or FRC (n=60). Morisky scores, health-related quality of life sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
(35 reference statements)
1
15
0
1
Order By: Relevance
“…The overall prevalence of adherence observed in the present study was similar to the ones reported in Brazil in earlier years 21,22 and worldwide 23,24,25 . Previous studies using the MMAS-8 with the same cut-off point as ours reported a prevalence of adherence of 43.7% 24 and 61.7% 25 , while studies using other self-report measurements of adherence reported rates above 70% 3,26,27 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall prevalence of adherence observed in the present study was similar to the ones reported in Brazil in earlier years 21,22 and worldwide 23,24,25 . Previous studies using the MMAS-8 with the same cut-off point as ours reported a prevalence of adherence of 43.7% 24 and 61.7% 25 , while studies using other self-report measurements of adherence reported rates above 70% 3,26,27 .…”
Section: Discussionsupporting
confidence: 91%
“…However, this method is fast, easy to apply and is a good predictor of virological failure 44 . Furthermore, several studies used the MMAS-8 to measure HAART adherence 23,24,25,35 and although there is a multiplicity of indirect measures of adherence, none of them is considered a "gold standard". The triangulation of methods increases the validity and reliability of the adherence results.…”
Section: (Continues)mentioning
confidence: 99%
“…A total of 66% of the studies employed prospective RCT design with some further elaborating the type of randomization, such as block stratified randomization and blinding strategy. Generally, those studies which employ prospective randomized control trial, [12][13][14][16][17][18][19][20]22 multicentered, 20,23 longer period of intervention evaluation with equal or more than 6 months 13,18,19,21,22 and having blinding approach 20 are better approaches to evaluate the effectiveness of an intervention. 26 Two studies which use retrospective approach 15,21 would create selection bias due to lacking randomization, where the significant difference between intervention and control groups is confounded with pre-existing differences between both groups.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that eight out of nine prospective randomized controlled studies are considered low-quality studies. [12][13][14][16][17][18][19][20]22 Such findings on the methodological quality could be arguably over-stringent as Zwikker et al also reported that all 30 included studies under review were judged as lowquality study with the use of the same judging framework. 27 On the other hand, the framework undeniably provides a clear guideline on designing a study with high quality methodology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation